Digital Marketing Strategy And Implementation Of Digital Payment Systems As A Trigger On Consumer Buying Interest: Case Study On Kopi Kenangan: Strategi Pemasaran Digital dan Implementasi Sistem Pembayaran Digital Sebagai Pemicu Minat Beli Ulang Konsumen : Studi Kasus pada Kopi Kenangan - Piter Hou; Irvan Rolyesh Situmorang (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2025)
This study aims to measure the influence of digital marketing strategies and the implementation of digital payment systems on customer repurchase intention for Kopi Kenangan in Medan Baru District, based on the issue of inconsistencies between online promotional promises and experiences at outlets that could potentially decrease customer loyalty. The research method applied is descriptive quantitative with a survey approach, involving 100 respondents selected through purposive sampling. The regression equation for Repurchase Intention = 1.933 + 0.252 Digital Marketing Strategy + 0.576 Digital Payment System + e indicates a positive influence from both variables. The research results show that digital marketing strategies and digital payment systems have a positive and significant impact on consumers repurchase intention. A coefficient of determination of 74% proves the contribution of the research variables to the repurchase intention. As a recommendation, Kopi Kenangan needs to align digital promotional content with service quality at the outlets, improve the stability and speed of the digital payment system verification, and provide employee training to ensure a consistent customer experience to strengthen loyalty and encourage repurchase.